Application of quorum quenching bacteria to membrane bioreactor for biofouling control - Ong, Chin Ee (2016)
Membrane bioreactor (MBR) is one of the widely-used wastewater treatment technologies, although biofouling remains as the biggest challenge, which can significantly decrease the efficiency of MBR. Solutions such as backwashing and air scouring are standard practices in industry; however, these measures are energy-intensive and decrease the productivity of MBR.